Inhibitory Effects of Ehretia tinifolia Extract on the Excessive Oxidative and Inflammatory Responses in Lipopolysaccharide-Stimulated Mouse Kupffer Cells - Jae Sung Lim; Sung Ho Lee; Hyosuk Yun; Da Young Lee; Namki Cho; Guijae Yoo; Jeong Uk Choi; Kwang Youl Lee; Tran The Bach; Su-Jin Park; Young-Chang Cho (MDPI AG, 2023)
Ehretia tinifolia (E. tinifolia) L., an evergreen tree with substantial biological activity, including antioxidant and anti-inflammatory effects, has been used in many herbal and traditional medicines. To elucidate its antioxidant and anti-inflammatory activity and the underlying mechanisms, we applied a methanol extract of E. tinifolia (ETME) to lipopolysaccharide (LPS)-stimulated mouse immortalized Kupffer cells. ETME suppressed the LPS-induced increase in nitric oxide, a mediator for oxidative stress and inflammation, and restored LPS-mediated depletion of total glutathione level by stabilizing antioxidative nuclear factor erythroid 2-related factor 2 (Nrf2) and the subsequent increase in heme oxygenase-1 levels. Furthermore, ETME inhibited the LPS-induced production of pro-inflammatory cytokines, including tumor necrosis factor-α, interleukin (IL)-1β, and IL-6. The inhibitory effects of ETME on pro-inflammatory responses were regulated by ETME-mediated dephosphorylation of mitogen-activated protein kinases (MAPKs: p38, p44/p42, and stress-associated protein kinase/c-Jun N-terminal kinase) and inhibition of nuclear localization of nuclear factor kappa B (NF-κB). These results suggest that ETME is a possible candidate for protecting Kupffer cells from LPS-mediated oxidative stress and excessive inflammatory responses by activating antioxidant Nrf2/HO-1 and inhibiting pro-inflammatory NF-κB and MAPKs, respectively.